Dynamic Feature Engineering for Breast Cancer Risk Stratification: A Machine Learning System Integrating Clinical Guidelines - Liao, Borui (Transactions on Computer Science and Intelligent Systems Research, 2025)
Breast cancer is one of the most common malignancies among women worldwide, posing a major public health challenge due to its high incidence and complex biological characteristics. Breast cancer screening is the cornerstone of tumor prevention and requires the systematic integration of morphological biomarkers and clinical guidelines. This study proposes a dynamic feature engineering framework, which encodes tumor biology through nonlinear transformations, including the square root transformation of tumor radius to simulate the growth of cubic volume ( , The risk decays along with age stratification. When evaluated on the Wisconsin Diagnostic Breast Cancer Dataset (WDBC), XGBoost performed very well in terms of clinical information characteristics, with an AUC of 0.90 (sensitivity =92%, specificity =88%), outperforming the 7.2% of the linear model. This transformation effectively linearizes the cubic relationship between tumor radius and volume. These results emphasize that combining algorithm design with oncological principles can enhance predictive accuracy while reducing unnecessary interventions, providing a blueprint for AI-driven precision oncology.